Prevalence of Sickle Cell Disease among Children aged 1 - 15 years attending the Sickle Cell Clinic at Luwero Hospital in Luwero District. A Cross-section Study. - Ivan Rodgers Matovu (Student's Journal of Health Research, 2022)
Background:  To determine the prevalence of sickle cell disease among children aged 1-15 years at Luwero Hospital in the Luwero district. Objectives: To determine the prevalence of sickle cell disease among children aged 1-15 years at Luwero Hospital in the Luwero district, to determine the average haemoglobin concentration among sicklers aged 1-15 years at Luwero Hospital, and to find out the effectiveness of health supervision and management of sicklers aged 1-15 years by their guardians in Luwero district. Study design:  The researcher conducted a cross-section study to obtain data among children aged 1-15 years attending the sickle cell clinic. Results:  The age of children ranged from 1-to 15 years with a mean age of6.9 years. The majority of the children were girls 66(68.75%). The majority of their parents/guardians were female 70(72.9%), divorced 57(59.4%), practicing farmers 43(44.8%) residing in rural areas 68(70.9%). Of the 96 children, 11 tested positive for SCD giving a prevalence of 11.5%. For haemoglobin concentration, the minimum Hb was 3.1 g/dl and the maximum Hb was 12.9g/dl with a mode of 5.6 g/dl for the blood samples that were analyzed with the CBC machine. Conclusion:  The prevalence of SCD was high as revealed to be 11.5% during the study period and the average Hb level was 6.8 g/dl with the modal Hb 5.6 g/dl and many children were heading to the severe form of SCA. Recommendation:  The government through the MOH should set aside funds to facilitate awareness projects encouraging premarital testing of couples for sickle cell trait and make it mandatory to curb the increasing prevalence of SCD and provide enough funds for much stock of medication for the sicklers to prevent early mortality and for better management and supervision.